Regional Distribution of Nitric Oxide Synthase in Human Anorectal Tissue: A Pilot Study on the Potential Role for Nitric Oxide in Haemorrhoids - Lohsiriwat, Varut; Wilson, Vincent G.; Scholefield, John H.; Dashwood, Michael R. (Current Vascular Pharmacology, 2020)
Objective: To study the distribution of nitric oxide synthase (NOS) isoforms and protein levels in human haemorrhoids and rectal tissue. Methods: Protein expression of NOS1, NOS2 and NOS3 was compared between haemorrhoids (n=14) and normal rectal submucosa (n=6) using Western blot analysis. The localisation of all NOS isoforms to specific structures was determined by immunohistochemistry. Results: Western blot analysis showed median (interquartile range) protein levels of all NOS isoforms were 1.5-2.4 times higher in haemorrhoids than rectal tissue; 121.4 (55.2-165.5) vs 50.0 (25.5-73.7) for NOS1 (p=0.020), 32.2 (23.8-140.6) vs 14.8 (9.6-34.0) for NOS2 (p=0.109), and 80.1 (62.0-139.5) vs 54.3 (48.7 -61.7) for NOS3 (p=0.015). Immunohistochemistry revealed a different distribution and location of all NOS isoforms in vascular and non-vascular structure of haemorrhoids and rectal tissues. The number of haemorrhoid specimens showing positive immunoreactivity of NOS in the vascular endothelium was significantly higher than that in rectal tissue for NOS1 (11/14 (79%) vs 1/6 (17%); p=0.018) and NOS3 (8/14 (57%) vs 0/6 (0%); p=0.042), but not for NOS2 (6/14 (43%) vs 4/6 (67%); p=0.63). Conclusion: Haemorrhoids have significantly higher protein levels of NOS1 and NOS3 than rectal tissue. The vascular endothelium of haemorrhoids also has significantly higher positive immunoreactivity of NOS1 and NOS3 than rectal tissue suggesting that blood vessels in haemorrhoids are exposed to higher NO concentrations than those of rectal tissue. Since haemorrhoids exhibit marked vascular dilatation and present with bleeding or swelling, a reduction in NOS - by applying NOS inhibitors - may potentially improve the symptoms of haemorrhoids.
Keywords: rectum